Horst Dietrich Preuss, Old Testament Theology, Vol. 2. Kentucky: Westminster John Knox Press, 1996. ISBN 0-664-21843-1 (Print). 431 halaman - Noh Ibrahim Boiliu (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2026)
This review examines the work of Horst Dietrich Preuss, Old Testament Theology Volume 2, which places the concept of election at the center of Old Testament theology. This study employs a critical analytical approach to the content and methodology of the book. The findings indicate that, theologically, Preuss successfully affirms God as the primary subject in Israel’s history and election as the foundation of identity and ethical responsibility. However, methodologically, the work reveals inconsistencies, as it shifts between historical approaches, word studies, and theological reflection without sufficient integration. This results in a lack of overall structural coherence. Nevertheless, the work remains a significant contribution to Old Testament theology, particularly in developing the concept of election as a basis for the ethical formation of faith communities. Therefore, the book is best engaged through critical and constructive reading within theological education contexts.